Recurrent pulmonary thromboembolism presenting with cardiac arrhythmias. Issue 3 (June 1979) - Brown, A K; Newton, P; Hamilton, E A; Anderson, V
Abstract : Pulmonary emboli seldom recur, and when recurrence does occur it is not associated with permanent sequelae unless there is progressive pulmonary arterial hypertension. Five patients with clinical and perfusion lung scan evidence of recurrent pulmonary embolism presented with abnormal cardiac rhythms without evidence of progressive pulmonary hypertension. Twenty-four-hour ambulatory electrocardiographic monitoring was valuable in diagnosis and in assessing the effectiveness of treatment. Although palpitation was the main complaint, other symptoms included tiredness, mild exertional dyspnoea, and chest discomfort unrelated to effort. Symptomatic improvement coincided with objective evidence of improvement from repeat lung scans and 24-hour ECG records. Antiarrhythmic agents controlled the arrhythmias but were subsequently withdrawn without the return of symptoms. Four of the five patients continued to take anticoagulants for two years. We believe that these five patients represent a group of patients with recurrent pulmonary emboli and a recognisable clinical picture dominated by arrhythmias unrelated to progressive pulmonary arterial hypertension. Long-term anticoagulant treatment was associated with clinical improvement.